Caste Distinction between Hinduism and Judaism - A comparative study- - Al-Maweed, Haya (Jordan Journal of Islamic Studies, 2023)
This research addresses the issue of caste-based distinction, which was rooted in Hinduism. This discrimination prevailed in Hindu society, which became divided according to the caste system that was dominant. We can find significant similarities between this and the Jewish caste-based discrimination, though the latter expanded to encompass a division within the Jewish community into two categories: one based on specific criteria, such as descent from a particular lineage, or being born to Jewish parents, while the second seeks to differentiate between Jews and other humans, known as "Goyim". Racial discrimination was prominent in both Hinduism and Judaism, with the aim of segregating humanity to an extent that is difficult to conceive. It led to looking at others based on factors like gender, color, professions, some religious considerations, and more. Caste-based discrimination represents a religious and social aspect that prevailed in both of these societies, resulting in many laws and duties for each caste that were characterized by their severity and disregard for human dignity.